PERISA Audio Visual Media on Learning Social Diversity for Class V Elementary School Students - Ketut Meli Astuti; I Made Suarjana; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2023)
The lack of innovative learning media development in the subjects of Pancasila and Civic Education (PPKn) has an impact on poor understanding of cultural concepts among students. This study aimed at developing effective local culture-oriented learning media for grade V elementary school students. This research used ADDIE learning media development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study consisted of 33 grade V elementary school students. The method applied in this study involved the use of questionnaires, rating scale sheets, and tests as research instruments. The research design used a pre-experimental approach. The results showed that the learning media developed, namely Media Adventure Negeri Indonesia (PERISA), is an audio-visual media in the form of videos that visualize the diversity of local cultures in Indonesia. PERISA media has a very high level of content validity with a score of 0.92. The response of teachers and students to PERISA media was also great, with a teacher response scored of 3.81 (declared very good) and a student response scored of 3.00 (declared good). The study also found significant differences on students' understanding of cultural concepts before and after using PERISA's audio-visual media. The implication of this study is that PERISA media is likely to increase the effectiveness of PPKn learning and provide convenience for students in understanding local cultural concepts. This media can be used as a supporting tool that has a positive impact on the learning process.